MỘT SỐ KẾT QUẢ NGHIÊN CỨU MỚI ĐẶC ĐIỂM PHÂN BỐ VÀ THÀNH PHẦN VẬT CỦA QUẶNG HÓA TRONG KHU VỰC MỎ CHÌ - KẼM NA SƠN - Niên, Bùi Ấn; Hòa, Trần Trọng; Anh, Trần Tuấn; Dung, Phạm Thị; Cẩn, Phạm Ngọc; Hiếu, Trần Văn; Hùng, Trần Quốc; Phượng, Ngô Thị (Vietnam Journal of Earth Sciences, 2011)
New reseach results on distributiion and compositional characteristics of the Na Son lead-zinc oreDetailed studies in structural geology, ore body distribution and ore component characteristics of the Na Son mine indicated:- The ore bodies in the first zone mainly composed of sphalerite, minority of galenite, chalcopyrite related tocarbonate-volcanic terrigenous sediment interposed of alternative extrusion. The ore body characterized by bed, vein, lenticle fit within surrounding rocks. Ore bed characteristics of replaced hydrothermal structure. The ore body almostdenuded as far as bottom.- The ore bodies in the second zone formed by galenite, less of sphalerite, chalcopyrite and ternadite lied in thetectonic fracture zone. The ore body characterized by vein occurred along clastic breccia, rock partings of syenitoid. The ore belong to filled hydrothermal. The top of ore body just exposed and potential part lied in the deep.The ore’s major elements characterized by high concentration of Zn (62.24-66.01 wt.%); Pb (86.76 wt.%), equivalent to rich Zn-Pb mine of the world.The ores have high content of rare elements such as: Cu (1-3 wt.%); Ag (10-123 ppm); Cd (66-1450ppm); In (0.7-31.5ppm); Mo (110-800 ppm), Sb (10.8-89.3 ppm, some time it reaches 323ppm); Bi (0.6-10.3 ppm),…Specific ratios of Zn/Pb in the ore in first zone: 0.25-31.14; in the second zone (0.067-0.92); Zn/Cd in the ore in first zone: 381.82-700; in the second zone (87.5-204.44) presented the ore in first zone denuded in the lower part, the ore in the second zone exposed in the higher part.